Blocking sense‐strand activity improves potency, safety and specificity of anti‐hepatitis B virus short hairpin RNA. Issue 9 (29th July 2016) - Michler, Thomas; Große, Stefanie; Mockenhaupt, Stefan; Röder, Natalie; Stückler, Ferdinand; Knapp, Bettina; Ko, Chunkyu; Heikenwalder, Mathias; Protzer, Ulrike; Grimm, Dirk
Abstract: Hepatitis B virus (HBV) is a promising target for therapies based on RNA interference (RNAi) since it replicates via RNA transcripts that are vulnerable to RNAi silencing. Clinical translation of RNAi technology, however, requires improvements in potency, specificity and safety. To this end, we systematically compared different strategies to express anti‐HBV short hairpin RNA (shRNA) in a pre‐clinical immunocompetent hepatitis B mouse model. Using recombinant Adeno‐associated virus (AAV) 8 vectors for delivery, we either (i) embedded the shRNA in an artificial mi(cro)RNA under a liver‐specific promoter; (ii) co‐expressed Argonaute‐2, a rate‐limiting cellular factor whose saturation with excess RNAi triggers can be toxic; or (iii) co‐delivered a decoy ("TuD") directed against the shRNA sense strand to curb off‐target gene regulation. Remarkably, all three strategies minimised adverse side effects as compared to a conventional shRNA vector that caused weight loss, liver damage and dysregulation of > 100 hepatic genes. Importantly, the novel AAV8 vector co‐expressing anti‐HBV shRNA and TuD outperformed all other strategies regarding efficiency and persistence of HBV knock‐down, thus showing substantial promise for clinical translation. Synopsis: RNAi is a powerful technology to suppress pathogens like hepatitis B virus (HBV), yet clinical translation requires better efficiency, safety and specificity. Here, a new solution is provided in the form of AAV vectors expressing anti‐HBV shRNAs together with an inhibitor of the shRNA sense strand. Hepatic AAV/shRNA expression yields potent target knockdown but can be toxic due to saturation of the RNAi pathway and off‐target dysregulation of cellular genes by the shRNA sense strand. One possible solution is to embed the shRNA in a miRNA scaffold, which reduces toxicity but also efficiency of HBV target knockdown. Alternatively, over‐expression of the rate‐limiting RNAi factor Ago2 from the same AAV vector can ameliorate toxicity without compromising efficacy. A novel strategy yielding best results is co‐delivery of a "tough decoy" (TuD) that blocks shRNA sense‐strand activity and concurrently enhances vector potency, safety and specificity in vivo . Abstract : RNAi is a powerful technology to suppress pathogens like hepatitis B virus (HBV), yet clinical translation requires better efficiency, safety and specificity. Here, a new solution is provided in the form of AAV vectors expressing anti‐HBV shRNAs together with an inhibitor of the shRNA sense strand.